Biomechanical testing of spinal segment fixed by thoracolumbar spine locking plate on the swine lumbar spine - Kočiš, Ján; Návrat, Tomáš; Florian, Zdeněk; Wendsche, Peter (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2010)
Background. The aim of the experiment was to compare the mechanical properties of intact spinal segment with impaired intervertebral disc and impaired intervertebral disc fixed by TSLP (Thoracolumbar Spine Locking Plate). Methods and results. Spinal specimens were taken from domestic swine. A total of 8 test mechanical states (intact, impaired and fixed) were modeled and the mechanical properties, expressed by the value of moment of couple necessary to twist the specimen at tensile force F = 200 N and the value of moments necessary for extension straining, were determined. The study was based on in vitro biomechanical testing of the TSLP plate used to stabilize the front thoracolumbar column of spinal segments taken from a pig. The plate was used for monosegmental fixation. The disc was cut by scalpel to simulate the Type A injury to front spinal column. In each state (intact, impaired or fixed), specimens were subjected to a tension load of prescribed force and, then, twisted by a given angle. Subsequently, extension load of intact, impaired and impaired & fixed segment was measured. Statistical evaluation verified the hypothesis of the different behavior of intact, impaired and fixed specimens – both for tension & torsion load and extension load. The analyses did not indicate different mechanical behavior of intact and fixed specimens. In other words, monosegmental fixation of both impaired and intact specimens by TSLP Synthes implant will lead to similar mechanical behavior of these specimens. Further, we found that intact and fixed specimens show non-symmetric behavior at positive and negative twisting angles. This was not observed for impaired specimens. Conclusion. Several stabilization systems were developed to stabilize the front thoracolumbar spinal column. Surgery of the anterior column of injured spine should restore the correct position of the spine, ensure decompression of vertebral canal when neural structures are compressed, and stabilize the spine to allow immediate loading and mobilization of the patient. The aim of this study was to compare mechanical properties of intact spinal segment, impaired spinal segment and impaired spinal segment stabilized by TSLP Synthes implant. The problems were solved by experimental modeling using a testing machine that simulated loads for several mechanical states of the spinal segment. Favorable mechanical properties of TSLP Synthes fixator were demonstrated. The experimental results will be used for subsequent computational modeling of the spinal segment in all experimentally solved states.
Keywords: financování organizované; Animals; meziobratlová ploténka; Financing, Organized; biomechanika; Bone Plates; kostní destičky; zvířata; Spinal Diseases; bederní obratle; Lumbar Vertebrae; Intervertebral Disc; nemoci páteře; Thoracic Vertebrae; Biomechanical Phenomena; hrudní obratle